Learning cycle 7E model to improve studying result and activity of IV grade students on natural science learning in SD Muhammadiyah Danunegaran of Yogyakarta - Irma Yulianti Budi Safitri; Ika Maryani; Dwi Sulisworo (JURNAL BIOEDUKATIKA, 2020)
This study aims to improve the activity and student learning outcomes after applying the Learning Cycle 7E learning model. This study uses classroom action research concerning the Kemmis and Taggart models, namely planning, implementation, observation, and reflection, which are carried out in three cycles. Data collection methods and instruments use the guidelines for observing student activities, guidance for observing teacher activities, tests of learning outcomes, and documentation. Data analysis techniques were carried out qualitatively (display, reduction, drawing/conclusion) and quantitatively (descriptive statistics). The results showed that student activity increased from cycle I by 93%, cycle II by 96%, and cycle III by 98.5%. Student's achievement increased from 74.16% to 91.67% (cycle I to cycle III). Classically, learning is said to be complete if 80% of students have reached the minimum completeness criteria, which is 75. This research shows that the stages in the Learning Cycle 7E can significantly increase student learning activities and outcomes.